The brazilian nuclear paradox - Lobo, Thadeu Marcos Orosco Coelho (2009)
Trabalho de Conclusão da Disciplina Arms Control and Disarmament- King's College of London, Master of Arts in Defense Studies, Reino Unido, 2009